Keratinocyte SR-B1 expression and targeting in cytokine-driven skin inflammation - Jacquelyn Trujillo; Andrea E. Calvert; Jonathan S. Rink; Bethany E. Perez White; Fabiola Sepulveda; Dauren Biyashev; Kurt Q. Lu; Robert M. Lavker; Han Peng; C. Shad Thaxton (Communications Medicine)
Abstract Background Strategies to treat inflammatory skin conditions require identifying new targets involved in interactions between overlying epithelial and underlying dermal immune cells. Scavenger receptor class B type 1 (SR-B1) is a cell surface receptor that binds high-density lipoproteins (HDL) and mediates inflammatory responses in immune and endothelial cells. The SR-B1 receptor is also expressed in keratinocytes, but its role in inflammatory skin diseases remains unexplored. Methods To investigate keratinocyte SR-B1 in the setting of inflammation, we measured its expression in skin biopsy samples obtained from patients with psoriasis; human skin explants exposed to the inflammatory cytokine, interleukin-17A (IL-17A); and mouse skin exposed to the pro-inflammatory agent, imiquimod (IMQ). We also evaluated the effects of SR-B1 knockdown on primary keratinocyte responses to IL-17A. Finally, we employed a synthetic HDL-nanoparticle (HDL NP) to investigate the therapeutic potential of targeting SR-B1 in IL-17A-stimulated keratinocytes and in male C57BL/6 mice with IMQ-induced skin inflammation. Results Our data show SR-B1 expression is increased in diseased human skin and in both human and mouse models of skin inflammation. SR-B1 knockdown in keratinocytes exacerbates the inflammatory response to IL-17A, whereas targeting SR-B1 with HDL NP attenuates this response. In the IMQ murine model, topical application of HDL NPs improves the skin phenotype, normalizes SR-B1 expression, and reduces molecular and cellular markers of inflammation. Conclusions Overall, SR-B1 plays a role in skin inflammation and HDL NP-mediated targeting of SR-B1 in keratinocytes may offer a targeted new therapy for inflammatory skin disease.